Faktor-Faktor Yang Mempengaruhi Kejahatan Berulang - Tugimin Supriyadi; Siti Nuriya Hikma; Sausan Salsabila; Siti Nurmala; Helta Puspasari (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This research aims to identify factors that influence repeat crime and explore prevention strategies that can reduce this tendency. Through a case study approach, this research analyzes several recidivism cases involving repeat offenders in Indonesia. Findings suggest that internal factors such as weak self-control and intimacy with religion, as well as external factors such as economic problems and negative social environments, play an important role in increasing the risk of recidivism. Criminological theories such as Social Structure Theory, Becker's Economic Theory, Opportunity Theory, and Social Learning Theory are used to understand the phenomenon of recidivism and identify effective prevention strategies. Based on the case analysis, comprehensive efforts are needed from various parties, including government agencies, communities, and non-profit organizations, to provide effective rehabilitation, increase supervision and social control, and provide social support to former drivers in order to reduce the risk of recidivism and strengthen community security overall.